Hearth - Tronin, Veniamin (Russia, 2013)
This is a movie about amateur actors and their Palace of Culture in a small town in Russia, trying to survive were the time is escaping from them.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films